An exploration of the barriers (socio-cultural) to successful implementation of PMTCT in Eastern Cape - Marutle, Lillian Dipuo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.